CURRICULUM CONTENT ORGANIZATION AND TEACHERS’ PERCEPTION OF ENTREPRENEURSHIP EDUCATION OF BASIC EDUCATION STUDENTS’ IN RIVERS EAST EDUCATIONAL ZONE OF NIGERIA - IseyechinboAdokiye, Godfrey-Kalio; Joy Chidinma, Duruamaku-Dim; Adokiye, Kalio, Godfrey (European Scientific Journal, ESJ, 2015)
A descriptive survey was conducted to investigate the curriculum content organization and teachers’ perception of entrepreneurship education on skills acquisition by Basic Education Students’ in Rivers East Educational zone of Nigeria. Two null hypotheses were stated to guide the study. The population for the study was 16,647 teachers and 19,737 students. Stratified sampling technique was adopted and the total sample size used was 1,664 teachers and 3,328 students bringing the total to 4,992. Two instruments titled “Curriculum Content Organization Questionnaire (CCOQ)” and “Acquisition of Entrepreneurship Skills Questionnaire (AESQ)” was used for data collection. Cronbach alpha reliability estimate was used to test the reliability. Data obtained were analysed using Pearson Product Moment correlation and Chi-square. Results of the study revealed a significant positive relationship between curriculum content organizationand teachers’ perception of entrepreneurship education on the acquisition of entrepreneurship skills by students. These variables had a positive influence on the acquisition of entrepreneurship skills in terms of making poultry feeds, soap and tie and dye of fabrics among the students. There is the need for students to possess entrepreneurship skills for employment generation, self-reliance and improved standard of living in the society. It is however recommended that in the planning and implementation of the curriculum, efforts should be made to make the learning experiences and contents of the curriculum relevant to the needs of the Nigerian society.